Do the Scandinavian consumers pay a 'fair' price for premium German white wines? - Jan Bentzen; Valdemar Smith (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2006)
The aim of this paper is to analyse the retail prices of premium German white wines sold in the Scandinavian countries. German white wines account for approximately 5-6 per cent of the total sale of wines - both red and white wines - in Denmark, Norway and Sweden. However, the market shares of German wines in Scandinavia have been declining for a number of years. Diminishing market shares may reflect changes in consumer taste or simply 'wrong' prices, the latter related to both the level of wine prices (German wines being relatively expensive) and the structure of wine prices. In general, country-specific price differences for identical wines may be caused by differences in taxes, different import prices, transportation costs as well as other costs - and also different competitive conditions at the retail level in the respective countries. Still, differences in wine prices across countries do not always reflect the above mentioned factors. The aim of this paper is to analyse further the relationship between the prices of German white wines in the Scandinavian countries and the prices in the country of production (Germany) by direct comparison (price level) and by using a hedonic price function approach (price structure). Using a sample of 150 German white wines being supplied on at least one of the national markets in Scandinavia the analyses suggest that the prices on German premium white wines on the Scandinavian markets are fair - both in terms of absolute average prices and in terms of relative prices.
Keywords: 330; Wein; Deutsch; Weinhandel; Hedonischer Preisindex; Schätzung; Nordeuropa